RETURN TO LITERATURE A MANIFESTO IN FAVOR OF THEORY AND AGAINST METHODOLOGICALLY REACTIONARY STUDIES (CULTURAL STUDIES, ETC.) - Bottiroli, Giovanni (2020)
What is literature for us today? And what will become of it in the nextfew years? Our era only seems willing to recognize the complexity of the field ofscience; whereas as far as literature is concerned, it is still thought that a rigorous training is not necessary and many deceive themselves into thinking that it is possible to do without the analytical tools created in the twentieth century and more recently thanks to theory.The refusal of theory is justified by the most tenacious prejudices, or simply by badfaith. It is believed (or some pretend to believe) that literary theory coincides with the years of structuralism, with the primacy of linguistics, and with the thesis of theintransitivity of language.Reality is quite different. Literary theory is a hybrid space where linguistics, rhetoric,philosophy and the theories of desire merge and interweave. In this space, whichundergoes constant renewal, literature is understood to be an intellectual andemotive experience, and an irreplaceable source of knowledge. Literary texts arestudied as dynamic objects that are able to cross the borders of the era in which theywere produced and enter the g”reat time (as Bakhtin called it).